Mountain of fire : the eruption and survivors of Mount St. Helens - Barone, Rebecca E. F. (Henry Holt and Company, 2024)
"Mountain of Fire is the narrative nonfiction story of the violent volcanic eruption of Mount St. Helens on May 18, 1980, the story of the people who died, those who survived, and the heroes who fought to raise an alarm. For weeks, the ground around Mount St. Helens shuddered like a dynamite keg ready to explode. There were legends of previous eruptions: violent fire, treacherous floods, and heat that had scoured the area. But the shaking and swelling was unlike any volcano ever seen before. Day and night, scientists tried to piece together the mountain's clues-yet nothing could prepare them for the destruction to come. The long-dormant volcano seethed away, boiling rock far below the surface. Washington's governor, Dixie Lee Ray, understood the despair that would follow from people being forced from their homes. How and when should she give orders to evacuate the area? And would that be enough to save the people from the eruption of Mount St. Helens?"--